DIGITALIZATION IN THE SERVICE OF CHILDREN IN THE REPUBLIC OF SERBIA: AN EXAMPLE OF THE "ČUVAM TE" PLATFORM - Ivanović, David (Metodička teorija i praksa, 2025)
The paper analyzes the process of digitalization in public administration, with a focus on the digital transformation of government services. Special attention is given to the role of digital tools in improving the education system and preventing peer violence. The theoretical framework includes defining digitalization and its application in the public sector, with a particular emphasis on educational institutions and authorities responsible for child protection. Through a case study of the national platform “I Protect You,” the paper examines the implementation of digital transformation and its effects on reducing violence among children. The results show that, over the first five years, the platform has become an important prevention instrument, while the increase in the number of reports indicates greater trust in institutional child-protection mechanisms and the development of a culture of nonviolence.